Uranyl extraction by N, N-dialkylamide ligands studied using static and dynamic DFT simulations. Issue 6 (20th November 2014) - Sieffert, Nicolas; Wipff, Georges
Abstract : DFT/MM-MD simulations highlight the structure and dynamics of mixed uranyl/nitrato/monoamides (L ) complexes at an "oil"/water interface. Abstract : We report DFT static and dynamic studies on uranyl complexes [UO2 (NO3 ) x (H2 O) y L z ] 2− x involved in the uranyl extraction from water to an "oil" phase (hexane) by an amide ligandL ( N, N -dimethylacetamide). Static DFT results "in solution" (continuum SMD models for water and hexane) predict that the stepwise formation of [UO2 (NO3 )2 L 2 ] from the UO2 (H2 O)5 2+ species is energetically favourable, and allow us to compare cis / trans isomers of penta- and hexa-coordinated complexes and key intermediates in the two solvents. DFT-MD simulations of [UO2 (NO3 )2 L 2 ], [UO2 (NO3 )2 (H2 O)L 2 ], and [UO2 (NO3 )(H2 O)L 2 ] + species in explicit solvent environments (water, hexane, or the water/hexane interface) represented at the MM or full-DFT level reveal a versatile solvent dependent binding mode of nitrates, also evidenced by metadynamics simulations. In water and at the interface, the latter exchange from bi- to monodentate, via in plane rotational motions in some cases. Remarkably, structures of complexes at the interface are more "water-like" than gas phase- or hexane-like. Thus, the order of U–ONO3 /U–OL bond distances observed in the gas phase (U–Onit < U–OL ) is inverted at the interface and in water. Overall, the results are consistent with the experimental observation of uranyl extraction from nitric acid solutions by amide analogues (bearing "fatty" substituents), and allow us to propose possible extraction mechanisms, involving complexation ofL "right at the interface". They also point to the importance of the solvent environment and the dynamics on the structure and stability of the complexes.